Pengaruh Persepsi Pelanggan Terhadap Implementasi Manajemen Mutu Dan Kualitas Produk Terhadap Kepuasan Pelanggan: Bukti Empiris Pada Pt Sarana Mega Fortuna Bandung - Rahmadini, Ayu Sri; Sutjipto, Mohammad Riza (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of customer perceptions of quality management implementation and product quality on customer satisfaction at PT Sarana Mega Fortuna Bandung, a garment manufacturer of Fluffy baby apparel. Using a quantitative explanatory design with a cross-sectional approach, data was collected from 85 respondents through purposive sampling and analyzed using PLS-SEM with SmartPLS. The results show that quality management implementation positively and significantly affects customer satisfaction (β = 0.481; p < 0.05), as does product quality (β = 0.352; p < 0.05). Both variables explain 68.4% of customer satisfaction, highlighting their strategic importance. Keywords: Quality Management Implementation; Product Quality; Customer Satisfaction; Customer Perception; Garment Manufacturing; PLS-SEM